Controlled release of simvastatin from biomimetic β-TCP drug delivery system. - Joshua Chou (Public Library of Science (PLoS), 2013)
Simvastatin have been shown to induce bone formation and there is currently a urgent need to develop an appropriate delivery system to sustain the release of the drug to increase therapeutic efficacy whilst reducing side effects. In this study, a novel drug delivery system for simvastatin by means of hydrothermally converting marine exoskeletons to biocompatible beta-tricalcium phosphate was investigated. Furthermore, the release of simvastatin was controlled by the addition of an outer apatite coating layer. The samples were characterized by x-ray diffraction analysis, fourier transform infrared spectroscopy, scanning electron microscopy and mass spectroscopy confirming the conversion process. The in-vitro dissolution of key chemical compositional elements and the release of simvastatin were measured in simulated body fluid solution showing controlled release with reduction of approximately 25% compared with un-coated samples. This study shows the potential applications of marine structures as a drug delivery system for simvastatin.